Análise de um sistema de custos fundamentado no ABC em uma indústria têxtil: estudo de caso - Silva, Marcone Venâncio da (2006)
This work has for objective suggest a model of results verifying for textiles companies makers of hammocks, based on the ABC (Activities Based Costing). The use of this tool was chosen because it’s about a system of cost capable of giving relevant and opportune information on the taken of business decisions. For the development of this study, was made a bibliographic research of the traditional and moderns systems and methods of cost, since we couldn’t understand the ABC system without its contextualization on the problematic of the systems and methods of traditional costs. From this bibliographic study, it was formed a conceptual base for application of the proposed model, comparing with the method of costing by absorvation. The method used on the research was the study of an only company, using sources of primary evidence, interviews, documental research and secondary data, as bibliographic research, articles, theses, and that has for objective show the viability of applying this technique in textile companies and be reference for the realization of equal studies, improving the scientifical knowledge of this managing tool for companies that wish to implant moderns systems for theirs costs. In the final part of this work, was made an analysis of the results of the comparison and, considering the objectives here said, it was possible to see the superiority of the ABC cost system comparing to te traditional (absorvation) method, because of the possibility of transparency of the connections resources-activities-products, minimizing the traditional dividing, allowing an actuation of the managers in the way to optimize the process and results.